Overexpression of PDE4A Acts as Checkpoint Inhibitor Against cAMP-Mediated Immunosuppression in vitro - Schmetterer, Klaus G.; Goldhahn, Katrin; Ziegler, Liesa S.; Gerner, Marlene C.; Schmidt, Ralf L. J.; Themanns, Madeleine; Zebedin-Brandl, Eva; Trapin, Doris; Leitner, Judith; Pickl, Winfried F.; Steinberger, Peter; Schwarzinger, Ilse; et al. (Frontiers in Immunology, 2019)
Malignant cells acquire physiological mechanisms of immunosuppression to escape immune surveillance. T-cell engineering to counteract this suppression is a major research interest to improve adoptive immunotherapy regimen. The intracellular second messenger cyclic AMP (cAMP) acts as a potent immunosuppressive signaling molecule in T-cells and is up-regulated by multiple tumor-relevant suppressive entities including prostaglandin E2 (PGE2), adenosine and several effector functions of regulatory T-cells. Consequently, we aimed to abrogate cAMP signaling in human T-cells by ectopic overexpression of phosphodiesterase 4A (PDE4A). We show that retroviral transduction of PDE4A into T-cells led to efficient degradation of cAMP in response to induction of adenylate cyclase. Retroviral transduction of PDE4A into CD4+ and CD8+ T-cells restored proliferation, cytokine secretion as well as cytotoxicity under immunosuppression by PGE2 and A2A-R agonists. PDE4A-transgenic T-cells were also partially protected from suppression by regulatory T-cells. Furthermore, PGE2-mediated upregulation of the inhibitory surface markers CD73 and CD94 on CD8+ T-cells was efficiently counteracted by PDE4A. Importantly, no differences in the functionality under non-suppressive conditions between PDE4A- and control-vector transduced T-cells were observed, indicating that PDE4A does not interfere with T-cell activation per se. Similarly, expression of surface markers associated with T-cell exhaustion were not influenced by PDE4A overexpression in long term cultures. Thus, we provide first evidence that PDE4A can be exploited as central immune checkpoint inhibitor against multiple suppressive entities.